Initiation and performance analysis of handoff in CDMA cellular systems / Rosmawati Abu - Abu, Rosmawati (2006)
This project presents an overview of soft handoff, an idea which is becoming quite important because of its use in the code division multiple access (CDMA) cellular standard. The study of handover performance in radio cellular system is based on simulation using software that was written in MATLAB. It involved a brief study of the various parameters affecting the handoff procedure. There are three major factors that affect the handoff. The factors are relative signal strength index (RSSI), carrier to interference ratio (C/I) and distance between mobile station (MS) and base station (BS).